The Rigid Amphipathic Fusion Inhibitor dUY11 Acts through Photosensitization of Viruses - Vigant, Frederic (American Society for Microbiology, 2014)
Rigid amphipathic fusion inhibitors (RAFIs) are lipophilic inverted-cone-shaped molecules thought to antagonize the membrane curvature transitions that occur during virus-cell fusion and are broad-spectrum antivirals against enveloped viruses (Broad-SAVE). Here, we show that RAFIs act like membrane-binding photosensitizers: their antiviral effect is dependent on light and the generation of singlet oxygen ((1)O(2)), similar to the mechanistic paradigm established for LJ001, a chemically unrelated class of Broad-SAVE. Photosensitization of viral membranes is a common mechanism that underlies these Broad-SAVE.